A Study on Data Security and Privacy Protection Issues in Cloud Computing - Chandramouli, N; Manjula, B (International Journal of Computer Sciences and Engineering, 2025)
Data security has a vital issue in cloud enlisting condition; it transforms into a noteworthy issue due to the data which is secured diversely completed the cloud. Data protection and security are the two essential parts of customer's stress in cloud information innovation. Different techniques as for these points of view are grabbing thought over the cloud preparing conditions and are investigated in both endeavors and scholastics. Data protection and security protection are transforming into the most enormous points of view for the future update and headway of cloud figuring innovation in the field of business and government parts. Thusly, in this paper, the cloud figuring security techniques are reviewed and its troubles as for data protection are discussed. The rule purpose of this proposed work is to update the data protection and security for the trustworthy cloud condition. This close research examination of the ebb and flow cloud security approach as for the data protection and security techniques utilized as a part of the cloud enrolling. It will be significant to enhance the security of data stockpiling in a cloud space.